The risk of early-onset neonatal sepsis in preterm infants with maternal histologic chorioamnionitis - IGK Winata Adnyana; Soetjiningsih Soetjiningsih (Indonesian Pediatric Society, 2005)
Background Chorioamnionitis, usually a subclinical condition, maycause preterm delivery and long-term morbidity.Objective The objective of this study was to determine the risk ofearly-onset neonatal sepsis in preterm infants with maternal histo-logic chorioamnionitis (HCA).Methods This was a prospective cohort study of preterm infantsborn at Sanglah Hospital, Denpasar from September 2002 to Feb-ruary 2004. Histopathological examinations of the subjects’ placen-tas were done and the infants were monitored for 72 hours for clini-cal signs of early-onset neonatal sepsis. Maternal and neonatal riskfactors were analyzed using multivariate statistical analysis.Results Eighty-two preterm infants were included, of which 41 werepositive for maternal HCA. Twenty-five (61%) of the infants posi-tive for maternal HCA developed early-onset neonatal sepsis, com-pared to 5 (12%) of those negative for maternal HCA (RR=5, 95%CI2.12;11.78). Nine infants died from early onset neonatal sepsis.Eight of them had positive HCA, and only one had negative HCA.The average length of hospital stay between infants with and with-out maternal HCA did not differ significantly [12.0 (SD 5.08) vs.12.6 (SD 1.34); P=0.80]. Logistic regression model analysis iden-tified only HCA as a significant risk factor for early-onset neonatalsepsis (OR=6.9, 95%CI 2.0;23). Gestational age (OR=1.3, 95%CI0.8;2.0), birth weight (OR=1.0, 95%CI 0.9;1.0), and neonatal as-phyxia (OR=1.0, 95%CI 0.1;4.4) were not found to be significantrisk factors.Conclusion Preterm infants with maternal histologicchorioamnionitis are at a higher risk for developing early-onsetneonatal sepsis